Phytochemical, cytotoxicity and antioxidant activities of the stem bark of Piper arborescens - Daniel, Nicholas; Fasihuddin Badruddin, Ahmad; Zaini, Assim; Chua Hun, Pin (Penerbit UTM, 2017)
Crude extract from stem bark of P. arborescens was fractionated by using column chromatography to isolate and purify its metabolite content. Six secondary metabolites were successfully isolated and their identification was performed by using Gas Chromatography - Mass Spectrometry (GC-MS), Nuclear Magnetic Resonance (NMR) and Fourier Transform Infrared (FTIR) spectoscopy. The isolated metabolites were identified as caryophyllene oxide (1), α-bisabolol (2), benzamide 2-(methylamino) (3), 2-ethylpiperidine (4), piperine (5) and methyl eugenol (6). Toxicity test on the four crude extracts of P. arborescens shows high cytotoxicity against Artemia salina brine shrimp with LC50 values ranging from 13.12 to 58.70 µg/mL. Greater cytotoxicity of the crude extracts of P. arborescens indicated the presence of potent cytotoxic components in this Piper spp. Antioxidant assay of P. arborescens against 2-diphenyl-1-picrylhydrazyl (DPPH) indicated moderate antioxidant activities of methanol, dichloromethane, chloroform and hexane crude extracts with EC50 values of 21.68, 23.82, 32.88 and 36.88 µg/mL, respectively. It is suggested that the six secondary metabolites identified in P. arborescens contribute as an active content for the cytotoxicity and antioxidant activities. This study showed that the crude extracts of P. arborescens is definitely having potential to be used as a source of natural product of various application